2020
DOI: 10.1097/brs.0000000000003526
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ossification of Posterior Longitudinal Ligament in Patients With Degenerative Cervical Myelopathy

Abstract: Study Design. A cross-sectional study. Objective. The aim of this study was to investigate the prevalence of ossification of posterior longitudinal ligament (OPLL) in patients with degenerative cervical myelopathy (DCM). Summary of Background Data. OPLL of the cervical spine is one of the main entities of DCM in Asian populations. However, few studies have reported the prevalence of cervical OPLL in DCM pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In particular, OPLL can be a common cause of myelopathy. Liao et al reviewed three-dimensional CT scans for 7210 patients with degenerative cervical myelopathy and showed that the prevalence of OPLL was as high as 18% [23]. However, Fujimori et al reviewed the registry data of OPLL patients and demonstrated that the prevalence of symptomatic OPLL was less than 1% in those with radiographically detected OPLL [21], demonstrating that most cases with radiographically detectable OPLL are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, OPLL can be a common cause of myelopathy. Liao et al reviewed three-dimensional CT scans for 7210 patients with degenerative cervical myelopathy and showed that the prevalence of OPLL was as high as 18% [23]. However, Fujimori et al reviewed the registry data of OPLL patients and demonstrated that the prevalence of symptomatic OPLL was less than 1% in those with radiographically detected OPLL [21], demonstrating that most cases with radiographically detectable OPLL are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…OSL is a characterized heterotopic ossification disease with multiple potential risk factors likely associated with its pathogenesis (2,3). Although several studies have explored the relationship between BMI and OSL, the results are conflicting and no definite conclusions have been obtained (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Our study integrated the existing evidence and revealed that the BMI of the OSL group was higher than that of the non-OSL group (P < 0.01), thereby indicating that a high BMI may increase the risk of OSL.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies focused on the OPLL (6,7,(9)(10)(11)(12)(14)(15)(16)(17) and four studies focused on the OLF (9,13,19,20) with respect to the types of OSL. Twelve studies containing 24,710 individuals explored the association between the BMI and onset of OSL (6,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and five studies on 797 OSL patients explored the association between the BMI and severity of OSL (7)(8)(9)(10)(11). Notably, Ikeda et al (11) and Endo et al (9) both simultaneously analyzed the relationship of BMI with the onset and severity of OSL.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations